The Ten(der) commandments : reflections on the Father's love - Mehl, Ron. (Sisters, Or. : Multnomah Publishers, 1998)
Once you've read Ron Mehl's reinterpretation of the Ten Commandments, you'll have a new understanding of the biblical context that defines these simple guidelines for living--not as harsh, restrictive rules, but as a tender love letter from a wise, all-knowing Father. Devoting a chapter to each commandment, Ron shows how God uses them to remove the confusion about right and wrong in today's relativistic culture, protect us from the consequences of our own moral weakness, and guide our thinking and actions in every situation.
On eagles' wings -- No other gods -- Pursuing empty images -- Take care with the name -- A time to reflect -- A command with a promise -- Removing the seeds of murder -- God's fence around your marriage -- Letting God meet your needs -- Words that wound, words that heal -- True contentment.
Includes bibliographical references (page 259).
Keywords: Ten commandments; God -- Love -- Biblical teaching